PENGARUH PENGGUNAAN PAYLATER, LITERASI KEUANGAN DAN SELF CONTROL TERHADAP PERILAKU KONSUMTIF MAHASISWA DI KABUPATEN BANJARNEGARA - Purbandari, Yenny; Indra Utami, Anita; Rudianti, Walid; Yubiharto, Yubiharto (Medikonis, 2025)
The use of Paylater is currently increasing along with the increasing use of the internet as a means of transaction. Low financial literacy and lack of self-control can affect consumptive behavior. This study was conducted with the aim of determining the influence of the use of paylater, financial literacy and self-control on the consumptive behavior of university students in Banjarnegara Regency. This study uses a quantitative method. The population in this study is university students in Banjarnegara Regency who are registered in PPDikti in 2023 through 4 universities in Banjarnegara Regency, namely STIE Tamansiswa Banjarnegara, Banjarnegara Polytechnic, STAI Tanbihul Ghofilin Banjarnegara and STIMIK Tunas Bangsa Banjarnegara with a total of 1960 students, while the sample used was 100 respondents. This study uses a purposive sampling technique. The data used were primary data and data collection techniques using questionnaires. The variables used are independent variables consisting of the use of paylater, financial literacy and self-control, while the bound variables are consumptive behavior. The data analysis technique used is multiple linear regression analysis. Based on the results of the study, partial tests show that the use of paylater has no effect on consumptive behavior, financial literacy has no effect on consumptive behavior, and self-control has an effect on consumptive behavior. The value of the determination coefficient is 0.205. This shows that the ability of independent variables to explain the dependent variable is 20.5%, while the remaining 79.5% is influenced by other variables that are not studied in this study.